The Determinants of Unemployment Insurance Participation: An Application of Theory of Planned Behaviour - Prima Zanellia, Quisty; Cahyadi, Eko Ruddy; Ermawati, Wita Juwita (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Unemployment is one of the economic disorders that affect the economic growth rate. In addition, the recent pandemic outbreak has turned the medical crisis into a global financial downturn, threatening the health and employment of people around the world. Unemployment insurance is intended to assist workers with partial and momentary income replacement, access to skill training, and job placement assistance during their unemployment period. The scheme was launched in Indonesia on March 2021. This study analyzed the intention effect toward participation and the effect of attitude, subjective norms, and perceived behavioral control towards the intention to participate using the Theory of Planned Behaviour. The total number of registered companies in DKI Jakarta Regional is 111.855, while the registered workers are 5.853.717. The quantity of samples based on the minimum sample calculation findings with the minimum number of samples obtained is 170 respondents. There were 200 participants of BPJS Ketenagakerjaan in the DKI Jakarta regional office who participated as respondents during the research period. SEM analysis methods are used in this study. The result showed that attitude toward behavior, subjective norms, and perceived behavioral control positively and significantly influence the intention to participate. Subjective norm is significant as an intervening variable between attitude and perceived behavioral control toward the intention to participate. Thus, strategies focusing on these factors can increase participation in the unemployment insurance scheme. Keywords: attitude toward behavior, participation intention, perceived behavioral control, subjective norm, unemployment insurance